PELAKSANAAN PERJANJIAN JUAL DAN SEWA BALIK (SALE AND LEASE BACK) ANTARA PT. INTAN BARUPRANA FINANCE DENGAN PT. KARYA ALAM LESTARI - Karnofa, Sa’dianti Nabila; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
An agreement is a legal event where one person promises another person or twopeople promise each other to do or not do something. One form of implementation of thisagreement is that which occurs between PT. IBF (PT. Intan Baruprana Finance) with PT.KAL (PT. Karya Alam Lestari). In the case of PT. IBF (PT. Intan Baruprana Finance)with PT. KAL (PT. Karya Alam Lestari), PT. IBF as lessor and PT. KAL, who then aslessee, entered into a Sale and Lease Back Agreement with the object of collateral beingtwo units of Factory Trailer Maunted Air Foam Package in 2012.This research is sociological legal research, it is based on field research whichrefers to information from interviews and observations as well as supporting documentsthat have a correlation with the background of the problem to be studied. This researchuses secondary data sources consisting of primary, secondary and tertiary legal materials.This research uses qualitative data analysis by producing a deductive method of drawingconclusions, namely drawing conclusions from general matters to specific matters.Based on the results and discussion that have been explained previously, theauthor draws the following conclusions: Implementation of the Sale and Lease BackAgreement that occurred between PT. IBF and PT. KAL is still not implemented properly.This is proven by several negligences made by the lessee during the agreement, such asnon-payment of the Financing Rent which should have been paid monthly in the amountof Rp. 388,239,248 (three hundred eighty eight million two hundred thirty nine thousandtwo hundred forty eight thousand) and the transfer of the position of 2 units of FactoryTrailer Maunted Air Foam Package without notification and confirmation to the lessor,and the financing object was found to be rusty and not well maintained . This fulfills therequirements for breach of contract in Article 13 of the Financing Lease Deed which hasbeen agreed upon by both parties.